Prinsip Kepastian Hukum Pemungutan Pajak Pertambahan Nilai Aset Kripto di Indonesia Berdasarkan Peraturan Menteri Keuangan Nomor 68/PMK.03/2022 - Syaharani, Meuthia (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
The recognition of cryptocurrency (hereinafter referred to Crypto Assets) as a commodity by the Commodity Futures Trading Supervisory Agency (Bappebti) creates legal consequences in the form of the taxation of Crypto Assets as a Taxable Item (BKP) that can be subject to Value Added Tax (VAT). The regulasi of VAT of Crypto Assets is regulated in the Regulation of the Minister of Finance Number 68/PMK.03/2022 on Value Added Tax and Income Tax on Crypto Asset Trading Transactions. The PMK regulates the object, subject, compliance, and rate of VAT on Crypto Assets. The arrangement regarding the material tax of PPN Crypto in the PMK certainly causes problems, because Article 23A of the 1945 Constitution pof the Republik of Indonesia explicitly states that the tax arrangement is governed by the law. Therefore, this research tries to analyze the principle of legal certainty in the collection of VAT on Crypto Assets in Indonesia based on PMK Number 68/PMK.03/2022. As wlell as the practice of collecting VAT on Crypto Assets do effectively increase Indonesia’s State Revenue. The method use in this research is normative jurisprudence by studying the principles of the formation of taxation law and legislation in the field of taxation. The data obtained is then analyzed qualitatively and the author will describe the results of the analysis descriptively. The results on this research show that PMK 68/PMK/03/2022 does not meet the principle of legal certainty in the information of legislation and regulations in the field of taxation. In addition, in increasing the state’s revenue through the collection of Crypto Asset VAT, The Ministry of Finance can make efforts to cooperate with other stakeholders and optimize architecture of technology.